Private Authority: INTERPOL Involvement in Malaysia's Political Case - Nur Karimah Jamili (Jurnal Hubungan Internasional, 2023)
This paper elaborates on the private authority which is focused on INTERPOL. Private authority is when nonstate actors create laws or norms that other important actors in international politics accept. There are three sources of authority which are market, moral and illicit authority. The aim of INTERPOLâ€™s establishment is to combat international crimes and facilitates international police collaboration and communication. The writer would like to discuss about â€œdoes INTERPOL exacerbate or ameliorate interstate conflict?â€. The thesis statement is INTERPOL ameliorate interstate conflict through the cooperation between its member states. INTERPOL usually acts as the middleman that provides information needed by the member states and also assists member states in arresting suspects. Through this paper, the writer will also state the case in which INTERPOL involve in Malaysia. This study will focus on the year 2006 until 2017. The year 2006 was chosen as it was the start of the Altantuya Shariibuuâ€™s case and the year 2017 was chosen as it was the latest year the case of 1MDB was discussed. These two cases were high-profile political case in Malaysia as it is said to involve Najib Razak, the former prime minister of Malaysia. Malaysia was chosen because through these two cases we can see the active involvement of INTERPOL as the private authority that helps its member state in solving the crime by offering a hand. Keywords: international political economy, INTERPOL, Malaysia, member states, private authority